A question of perspective. How Portuguese voters see and act in European elections - Cunha, Alice (2008)
Thirty four years ago (before the end of the Portuguese dictatorship regime), the Portuguese people barely knew its European neighbours, had a pragmatic attitude concerning economic aspects, and a distant one regarding a more close political understanding. After 1974 this position changed and, twelve years later, in 1986, when Portugal became the European Union 11th member-State, Europe started to be regarded in a different way. In this paper, is it our intention to see how Portuguese people have expressed its feelings about the European Union in a very specific moment: the European elections. In this sense, in a political-sociological frame, we are going to analyse the five European elections (1987, 1989, 1994, 1999 and 2004) in which the Portuguese participated. Using theoretical tools of the Political Sociology, we seek to understand the whys and the who’s for a very poor participation in this type of elections. This paper will be based not only in published articles and books about European elections, and in the results itselfs, but also in the opinions expressed in several Eurostat questionnaires.